PEMBELAJARAN MENULIS TEKS FABEL MENGGUNAKAN METODE BROKEN SQUARE BERBASIS CERITA BERGAMBAR - Nurul Sobia; R Ika Mustika (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Writing fable texts on the learning of junior high school students can be categorized into difficult lessons. Because students are required to be able to rew write stories according to their language structure and rules. Students find it hard to imagine pouring out their ideas. This causes students to become less excited about Learning Indonesian. In this study, researchers found that students' difficulties with learning to write fable texts were still difficult in pouring their imagination into writing the fable text. It is still rare for students to apply the language rules and structure of the fable text. The purpose of this study is to improve the writing ability of students in pouring their imagination into a writing. This research was conducted by applying broken square method assisted by pictorial story. This method directs students to play puzzles or compose fragments of images that have been shared by the teacher and then students are directed to arrange the fragments into a whole image medium. This method is used to build the spirit and creativity of students so as not to get bored in writing skills. As for the results of the study obtained, researchers conducted a pre-test whose results are still many students who do not yet understand the elements and language rules of the fable text. After the use of broken square method, the writing results of students are much better than before the applied broken square method.